Chaetomitrium Poecilophyllum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are robust and densely pinnately branched; (2) branch leaves are flexuose, to 2.7 mm long, slightly plicate, apices are gradually long-acuminate and wavy; (3) leaf margins are incurved on one side, serrate above and denticulate below with simple teeth; (4) costae are distinct; (5) lamina cells are strongly thick-walled, porose and smooth; (6) setae are 15 mm long, slightly papillose above and gradually smooth below; (7) calyptrae cucullate, hispid all over, hairs gradually shorter below and bases are naked.